Nahdlatul Ulama’s Strategies for Countering Radicalism in Indonesia: A Cultural and Religious Educational Approach - Encep Sehabudin (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This research is motivated by the increasing spread of religious radicalism in Indonesia which has the potential to threaten social harmony, the integrity of the nation, and moderate Islamic values that have taken root in people's lives. In this context, Nahdlatul Ulama (NU) as the largest religious organization in Indonesia has a strategic role in counteracting radicalism through cultural and religious educational approaches. This research aims to analyze NU's strategy in preventing and overcoming radicalism, especially through strengthening moderate Islamic values (wasathiyyah), developing education based on local traditions, and internalizing the teachings of Ahlussunnah wal Jama'ah. The research methodology used is a qualitative approach with a descriptive-analytical type of research. Data was collected through literature studies of NU's official documents, books, and scientific journals, and supported by interviews and observations of NU's educational practices and religious activities at the grassroots level. Data analysis techniques are carried out by means of data reduction, data presentation, and thematic conclusion drawn. The findings of the study show that NU's strategy in countering radicalism is carried out through several main approaches, namely: (1) cultural education based on pesantren traditions, religious practices, and local wisdom; (2) strengthening the curriculum and moderate Islamic da'wah that emphasizes the values of tasamuh (tolerance), tawazun (balance), and i'tidal (justice); and (3) the development of educational and da'wah institutional networks that are adaptive to contemporary challenges. This strategy has proven effective in building people's ideological resilience to radical ideas and strengthening a peaceful and inclusive Islam in Indonesia.